Pelaksanaan Analisis Jabatan Untuk Meningkatkan Efektivitas Kerja Perangkat Desa - Sofiani, Nisha Faradilla; ahmad, Fandi; Supriatna, Metha Djuwita (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2023)
Village workers, including village workers in Cisondari Village, are the main source of competitive advantage in village government because they are responsible for carrying out village government duties and functions as well as empowering village communities. Cisondari Village is located in Bandung Regency's Pasirjambu District. A job information document, compiled through job analysis, is required to assist job holders in understanding their work. One of the issues that arises in this village is the lack of job information for village workers. This causes an imbalance in the workload and has an impact on the work effectiveness of village workers, which in turn has an impact on organizational performance. As a result, job analysis activities are required to collect information about the duties and functions of each position in Cisondari Village. This activity is divided into two parts: advocacy and workshops. Advocacy is provided to village officials in the form of oral presentations on job analysis. Meanwhile, the workshop is delivered in the form of practice in preparing a job analysis, accompanied by a team. An evaluation was conducted to determine the usefulness of community service activities. The evaluation results revealed that the participants felt a high level of satisfaction and benefits from the activity. Furthermore, service activities are thought to be beneficial for village workers because they can help solve problems in Cisondari Village.